GlyphSR: A Simple Glyph-Aware Framework for Scene Text Image Super-Resolution - Wei, Baole; Zhou, Yuxuan; Gao, Liangcai; Tang, Zhi (Proceedings of the AAAI Conference on Artificial Intelligence, 2025)
The goal of scene text image super-resolution (STISR) is to enhance the clarity of text within line images, thereby improving readability and enabling more accurate text recognition. However, existing STISR methods often rely heavily on Text Prior (TP) derived from trained recognizers, which can be unreliable and may lead to incorrect glyph restoration. Text images contain two crucial types of information: semantic content from word meanings and structural details from glyphs. When semantic information is unreliable, accurate perception of glyph structures becomes essential. This paper introduces GlyphSR, a novel STISR framework that addresses three key challenges: precise extraction, effective learning, and optimal utilization of glyph structural information. GlyphSR incorporates the Glyph Extraction Module (GEM), a training-free approach leveraging the Segment Anything Model (SAM) to accurately extract character-level glyphs. The Glyph Perception Module (GPM) models and learns glyph structures through segmentation and classification tasks, while the Glyph Fusion Module (GFM) integrates glyph information to enhance overall STISR model performance. Extensive experiments on the TextZoom dataset demonstrate that GlyphSR achieves a new state-of-the-art performance.